Analysis of Factors Affecting Profitability in Indonesian Sharia Commercial Banks in 2016 -2020 - HAIRIZA SATIA HAIRIZA (Journal of Islamic Economic and Business Studies, 2023)
The purpose of this study is to examine the effect of Capital Adequacy Ratio (CAR), Non-Performing Finance (NPF), Operating Costs to Operating Income (BOPO), and Return On Assets (ROA) in Islamic Commercial Banks in Indonesia in 2016 -2020. This research uses 13 companies registered with the Financial Services Authority (OJK) from 2016 -2020. Data were processed using Eviews 10. The results of this study show that partial Capital Adequacy Ratio (CAR) has no positive effect on Return On Assets (ROA), Non-Performing Finance (NPF) has no positive impact on Return On Assets (ROA), Operational Costs on Operating Income (BOPO) has a positive effect on Return On Assets (ROA), and Finance to Deposit Ratio (FDR) has no positive impact on Return On Assets (ROA). And simultaneously, Capital Adequacy Ratio (CAR), Non-Performing Finance (NPF), Operating Expenses to Operating Income (BOPO), and Finance to Deposit Ratio (FDR) all have a positive effect on Return on Assets (ROA).